MOLECULAR IDENTIFICATION OF LOCAL VERTEBRATE SPECIES USING CYTOCHROME OXIDASE SUBUNIT I (COI) GENE - Che Lah, Ernieenor Faraliana; Tsolmon, Amartuvshin; Ahamad, Mariana (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
The aim of this study is to determine a molecular tool for identification of local vertebrate species using mtDNA COI gene. Polymerase Chain Reaction (PCR) using universal primers complementary to the conserved region of the mitochondrial DNA (mtDNA) cytochrome oxidase subunit I (COI) gene fragment, was performed on DNA of blood samples of 30 local animals in Malaysia. DNA of hosts was amplified by PCR and the products were visualized on gel electrophoresis. Twenty two sequences (73.3%) were obtained and compared with sequences registered in GenBank and BOLD Systems databases. The BLAST results for fifteen samples (68%) showed sequences were in congruence with morphological identification at 92% to 100% accuracy while seven sequences had no significant similarity. These results suggest that COI-based PCR is a reliable identification tool for vertebrates and can be applied for epidemiological studies on blood meal analysis of arthropod in Malaysia.